2020
DOI: 10.1088/1361-665x/abb21c
|View full text |Cite
|
Sign up to set email alerts
|

Study on the rheological properties and polishing properties of SiO2@CI composite particle for sapphire wafer

Abstract: To study the rheological properties and polishing performance of magnetorheological fluids (MRFs) prepared with SiO2@carbonyl iron (CI) core-shell particles, SiO2@CI core-shell particles with different shell thicknesses were synthesized by an improved Stöber method controlling the amount of tetraethyl orthosilicate (TEOS). Then, four types of MRFs which dispersed with core-shell particles with thin shells, core-shell particles with thick shells, SiO2 particles, or carbonyl iron were prepared for sapphire polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Table 1 presents the experimental conditions in detail. During the test, 10 sct simethicone, SiO2@CIP composite particles with an average particle size of 4 μm, and diamond abrasives with an average particle size of 0.25 μm are uniformly dispersed at ratios of 70 wt%, 25 wt%, and 5 wt% and prepared into an MER fluid, in which SiO2@CIP composite particles have satisfactory electrorheological effect and magnetorheological effect characteristics (Pan et al, 2020a). As shown in Figure 6, after processing, a surface profiler (TALOR HOBSON PGI1240) is used to measure the surface profile along the AB direction, and a white light interferometer (BRUKER Contour GT-X) is used to measure the surface roughness and surface topography.…”
Section: Magnetoelectric Synergistic Rheological Finishing Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the experimental conditions in detail. During the test, 10 sct simethicone, SiO2@CIP composite particles with an average particle size of 4 μm, and diamond abrasives with an average particle size of 0.25 μm are uniformly dispersed at ratios of 70 wt%, 25 wt%, and 5 wt% and prepared into an MER fluid, in which SiO2@CIP composite particles have satisfactory electrorheological effect and magnetorheological effect characteristics (Pan et al, 2020a). As shown in Figure 6, after processing, a surface profiler (TALOR HOBSON PGI1240) is used to measure the surface profile along the AB direction, and a white light interferometer (BRUKER Contour GT-X) is used to measure the surface roughness and surface topography.…”
Section: Magnetoelectric Synergistic Rheological Finishing Experimentsmentioning
confidence: 99%
“…Feng et al (2020a) prepared a magnetic composite fluid (MCF) with α-cellulose in which α-cellulose and clustered cellulose were interwoven to increase the strength of the polishing pad and improve the influence of abrasives on the surface of the workpiece. Pan et al, 2020a prepared SI@CIP composite particles by combining abrasives and dispersed particles into a complex, which could effectively solve the problem of abrasive utilization. However, due to the difficulty of preparing composite particles and the high cost, better methods are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, apart from the high cost of equipment, the processing efficiency of the MR polishing method is very low. In our previous work, our research group proposed a cluster MR polishing technology with 'the flexible polishing pad' formed by the cluster MR fluid [18][19][20]. Compared with the traditional MR polishing method, the surface roughness Ra of the single-crystal sapphire polished by the cluster MR polishing decreased from 1.36 nm to 0.76 nm, and the MRR increased from 4.37 to 9.53 nm min −1 [21].…”
Section: Introductionmentioning
confidence: 99%
“…CMP can realize the smooth and flat processing of GaN crystals, but its efficiency needs to be improved further. Magnetorheological finishing is a non-damage processing technology [21][22][23][24][25], which can effectively realize sub-nanometer processing of hard and brittle crystal materials such as sapphire [26,27], silicon carbide [28,29], and optical glass [30][31][32]. However, research on GaN magnetorheological finishing has not been reported.…”
Section: Introductionmentioning
confidence: 99%